2009
DOI: 10.3201/eid1504.080891
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Dengue and Malaria in Cayenne Hospital, French Guiana

Abstract: Dengue-malaria co-infection reports are scarce. Of 1,723 consecutive febrile patients in Cayenne Hospital, 238 had dengue (174 early dengue fever cases) and 393 had malaria (371 acute malaria); 17 had both. Diagnosis of 1 of these 2 infections should not rule out testing for the other infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
87
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(92 citation statements)
references
References 13 publications
4
87
0
1
Order By: Relevance
“…In a series of 17 confirmed co-infection cases in French Guiana with an epidemiological profile similar to our Manaus, thrombocytopenia was the major complication observed in retrospective data from emergency room patients. 4 Severe anemia was observed in 1 of 11 patients and required red blood cell transfusion. The clinical use of hemoglobin/ hematocrit as a severity marker in concurrent DENV and malaria infection could be tricky and may cause some misinterpretation, considering that both diseases impact red blood cell count through different mechanisms that should be addressed individually.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a series of 17 confirmed co-infection cases in French Guiana with an epidemiological profile similar to our Manaus, thrombocytopenia was the major complication observed in retrospective data from emergency room patients. 4 Severe anemia was observed in 1 of 11 patients and required red blood cell transfusion. The clinical use of hemoglobin/ hematocrit as a severity marker in concurrent DENV and malaria infection could be tricky and may cause some misinterpretation, considering that both diseases impact red blood cell count through different mechanisms that should be addressed individually.…”
Section: Discussionmentioning
confidence: 99%
“…In French Guiana, a retrospective study with 1,740 patients with acute febrile syndrome identified six confirmed concurrent infection cases, with malaria diagnosis made by thick blood smear and DENV infection diagnosed by positive reverse transcription-polymerase chain reaction (RT-PCR) or viral isolation. 4 In that study, P. vivax and DENV serotype 3 (DENV-3) were responsible for the majority of the co-infections. In Brazil, in the Amazon region, DENV-2 was detected in sera from two patients living in the Eastern Brazilian Amazon that also presented with acute P. vivax infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aproximadamente, 200 arbovírus foram isolados no Brasil, e 40 estão associados com doenças em humanos. Quatro destes 40 são considerados ser de importância para a saúde pública no Brasil: vírus da dengue (1)(2)(3)(4), Oropouche, Mayaro e febre amarela. Juntamente com estes vírus, aproximadamente 98% dos casos de malária estão restritos à região da Amazônia Legal.…”
Section: Introductionunclassified
“…As illustrated by articles in this issue about adiaspiromycosis (2), malaria (3,4), dengue (4), Chagas disease (5), Kaposi sarcoma-associated herpesvirus (6), suspected Brazilian purpuric fever (7), and other infections, new diseases continue to emerge and old ones continue to undergo epidemiologic change throughout the vast Amazon River basin.…”
mentioning
confidence: 99%